Identification of Flood-Prone Areas Using the Topographic Wetness Index Method in Fena Leisela District, Buru Regency - Philia Christi Latue; Heinrich Rakuasa (Journal Basic Science and Technology, 2023)
Fena Leisela District is often hit by floods in the rainy season. Floods that often occur in Siwalalat District are caused by the overflow of the Waegeren River. Research using DEMNAS data and analysis using the Topographic Wetness Index method. The results of the analysis of the inundation potential are divided into three classes, namely the low potential class with an area of 92,196.09 or 63.04%, the medium class covering 45,769.48 ha or 31.29% and the high potential class covering 936.12 ha or 5.67 %. The research results are expected to be a reference for the government and the community in handling future floods to minimize the impact that occurs